PENENTUAN HARGA POKOK KAMAR DENGAN METODE ACTIVITY BASED COSTING: STUDI KASUS PADA HOTEL AL-FATH SYARIAH KOTA JAMBI - Kisan Desvalingga (Nusantara Hasana Journal, 2025)
This study focuses on a comparative analysis of the Activity-Based Costing (ABC) method and the traditional method applied at the Al-Fath Syariah Hotel in Jambi City to determine room rates. Using a qualitative-descriptive approach and primary and secondary data, this study identified significant differences in the room rate calculations between the two methods. The traditional method, which only allocates indirect costs based on volume, tends to be less accurate and can lead to cost distortions. In contrast, the ABC method, which allocates costs based on resource-consuming activities, provides more relevant and accurate cost information. A detailed analysis shows that the largest differences occur in room types with more complex facilities and activities, such as Family Rooms, where actual overhead costs are higher but not identified in the traditional method. The implication of this study is the importance for hotel management to adopt an activity-based costing approach as a basis for more informed strategic decision-making, particularly in pricing and cost control.